2010
DOI: 10.1021/ac902881m
|View full text |Cite
|
Sign up to set email alerts
|

Model Updating for Spectral Calibration Maintenance and Transfer Using 1-Norm Variants of Tikhonov Regularization

Abstract: In this study, calibration maintenance confronts the problem of updating a model developed in the primary condition to accurately predict the calibrated analyte in samples measured in new secondary conditions. Calibration transfer refers to updating a model based on a primary instrument to predict samples measured on new secondary instruments. A 2-norm variant of Tikhonov regularization (TR) has been used with spectroscopic data to perform calibration maintenance and transfer where just a few samples measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 34 publications
1
68
0
Order By: Relevance
“…The methods studied in this paper are three variants of Tikhonov regularization (TR) [24,25] used for calibration maintenance and transfer [26,27]. One of the TR variations is restricted to vector 2-norm minimizations [26] and the other two new adaptations of TR were recently developed to include 1-norm vector minimizations [27]. Results can improve with the 1-norm compared to those reported for TR in 2-norm.…”
Section: Introductionmentioning
confidence: 99%
“…The methods studied in this paper are three variants of Tikhonov regularization (TR) [24,25] used for calibration maintenance and transfer [26,27]. One of the TR variations is restricted to vector 2-norm minimizations [26] and the other two new adaptations of TR were recently developed to include 1-norm vector minimizations [27]. Results can improve with the 1-norm compared to those reported for TR in 2-norm.…”
Section: Introductionmentioning
confidence: 99%
“…7, we hope to immunize the primary calibration model against spectral noise while simultaneously performing wavelength selection. This augmentation forms the basis of many recent calibration transfer and maintenance methods [33][34][35] including augmented classical least-squares procedures, which decompose spectra into pure-component concentrations and pure-component spectra. [36][37][38][39][40] More recently, a comprehensive review of two-norm and one-norm penalties for sparse multivariate calibration and maintenance was undertaken by Kalivas.…”
Section: Calibration Maintenance Andmentioning
confidence: 99%
“…Not surprisingly, the number of update samples needed to span the new effects, as well as their optimal placement in the calibration model, varies with the number of samples in the original calibration model and with the amount of correction required to make the model useful to predict on spectral responses from the secondary instrument. Previous work has shown that, for similar instruments and for small calibration sets, a portion of the original calibration used as update samples, comprising 25-33% of the original calibration selected using a Kennard-Stone design and measured on the secondary instrument, is sufficient to obtain a global calibration model with performance similar to that of the original, single-instrument calibration model [7,14,15]. The update standards need not match those used in the original calibration, but with a large calibration set, it is necessary to either have many update standards or to weight them so that the update samples contribute sufficiently to the global model [9,10].…”
Section: Transfer Of Calibration Using Model Updating and Orthogonal mentioning
confidence: 99%